Circulating ACTH and related peptides in lung cancer. - Ratcliffe, J. G. (Nature Publishing Group, 1982)
The prevalence of high levels of circulating ACTH-like immunoactivity was determined in 134 patients with lung cancer, using reference ranges from 52 age- and sex-matched patients with non-malignant lung disease. Two studies used ACTH radioimmunoassays with different specificities. Study A used an unextracted plasma or serum assay for total ACTH immunoactivity. High serum ACTH levels occurred in 24% of patients with small-cell carcinoma and 3% of patients with non-small-cell cancer. In patients with small-cell carcinoma, levels were high in 12% with limited disease and 32% with extensive disease. Study B used an ACTH assay after plasma extraction by porous glass, which measured mainly regular 1-39 ACTH. Here no lung-cancer patient had levels above the reference range, suggesting that the high levels in Study A may be due to plasma ACTH components which are poorly extracted by porous glass. It is concluded that high circulating ACTH immunoactivity occurs in a minority of patients with lung cancer, particularly those with extensive small-cell carcinoma. Indirect evidence suggests that the high ACTH levels detected with assays for total ACTH are due to molecular forms other than 1-39 ACTH, probably high-mol.-wt species.